2014
DOI: 10.1111/bdi.12171
|View full text |Cite
|
Sign up to set email alerts
|

Using the Brief Assessment of Cognition in Schizophrenia (BACS) to assess cognitive impairment in older patients with schizophrenia and bipolar disorder

Abstract: The BACS appears to be a feasible and informative cognitive assessment tool for elderly patients with bipolar disorder. We believe that these preliminary results merit further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 67 publications
1
19
0
Order By: Relevance
“…We found 53 articles on OABD in the last 6 years . Of those, 50 (94%) papers examined clinical samples ranging from 10 to 315 subjects (total of 3302 subjects, mean ± standard deviation (SD) 62.3 ± 51.5 subjects/paper, median 53 subjects/paper).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We found 53 articles on OABD in the last 6 years . Of those, 50 (94%) papers examined clinical samples ranging from 10 to 315 subjects (total of 3302 subjects, mean ± standard deviation (SD) 62.3 ± 51.5 subjects/paper, median 53 subjects/paper).…”
Section: Resultsmentioning
confidence: 99%
“…All studies ( n = 53) reported age and gender. Levels of education were the next most often reported ( n = 34 studies, 64%), followed by ethnicity ( n = 23, 43%) and marital status ( n = 17, 32%) …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations